Fossil otoliths, from the Gulf of Kutch, Western India, as a paleo-archive for the mid- to late-Holocene environment. (18th March 2016) - Amekawa, Shota; Kubota, Kaoru; Miyairi, Yosuke; Seki, Arisa; Kawakubo, Yuta; Sakai, Saburo; Ajithprasad, P.; Maemoku, Hideaki; Osada, Toshiki; Yokoyama, Yusuke
Abstract: Abundantly available catfish otoliths excavated from the ruins of the Indus civilization, in the coastal regions of Western India, are expected to preserve a detailed paleoclimatological record of the mid- to late-Holocene. In this study, we analyzed saltwater catfish otoliths recovered from the Gulf of Kutch, Western India. Stable isotopes (oxygen and carbon) and elemental ratios (Ba/Ca and Sr/Ca) were measured by isotope ratio mass spectrometry (IRMS) and high-resolution laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), respectively. Oxygen isotopes of a modern otolith (δ 18 O) indicates the interval when the catfish would have dwelt in the sea and appear to record seasonal temperature variability with a precision of 1 C°. Calculated temperatures from δ 18 O of a fossil otolith dated to 4.3 cal ka BP indicates that the minimum temperature in winter was ∼2.5 C° lower than that of the present. Although comparison to alkenone results from the northwestern Arabian Sea indicates potential temperature underestimation, further measurements of modern and fossil samples would lead to more precise reconstruction of temperature history during mid- to late- Holocene.